2021
DOI: 10.1371/journal.pone.0244886
|View full text |Cite
|
Sign up to set email alerts
|

The association of chest radiographic findings and severity scoring with clinical outcomes in patients with COVID-19 presenting to the emergency department of a tertiary care hospital in Pakistan

Abstract: Introduction While chest x-rays (CXRs) represent a cost-effective imaging modality for developing countries like Pakistan, their utility for the prognostication of COVID-19 has been minimally explored. Thus, we describe the frequency and distribution of CXR findings, and their association with clinical outcomes of patients with COVID-19. Methods All adult (≥ 18 years) patients presenting between 28th February-31st May to the emergency department of a tertiary care hospital in Pakistan, who were COVID-19 posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 11 publications
7
44
1
Order By: Relevance
“…On logistic regression analysis, the maximum RALE score (0.0932 [0.024–0.367]) was found to be a predictor for discharge (recovery) of patients. In our study, the maximum RALE score predicted the death of patients (10.730[2.727–42.206]) ( Figure 6 ), and it was consistent with the study conducted by Kaleemi et al [ 7 ]. The CXR severity score (Brixia score, 0 to 18) designed by Borghesi et al predicted mortality in the same way [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…On logistic regression analysis, the maximum RALE score (0.0932 [0.024–0.367]) was found to be a predictor for discharge (recovery) of patients. In our study, the maximum RALE score predicted the death of patients (10.730[2.727–42.206]) ( Figure 6 ), and it was consistent with the study conducted by Kaleemi et al [ 7 ]. The CXR severity score (Brixia score, 0 to 18) designed by Borghesi et al predicted mortality in the same way [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed a statistically significant correlation between maximum RALE score and clinical outcome of the patients ( Table 3 ). The maximum RALE score was positively and significantly correlated with age ( r = 0.721) ( Figure 5 ), and it was consistent with the studies conducted by Kaleemi et al and Salmeron et al [ 7 , 15 ]. The maximum RALE score was positively correlated with the length of hospital stay and the death of patients, and it was consistent with the study conducted by Kaleemi et al [ 7 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations